L’informazione geografica nella regione Toscana - Maurizio Trevisani; Umberto Sassoli (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
The Tuscany region, made possible consult and download geographic informations through Creative Commons license, to facilitate the access to geographic database that produce. All this is possible through the GEOScopio WMS.